2, 5-dimethylcelecoxib improves immune microenvironment of hepatocellular carcinoma by promoting ubiquitination of HBx-induced PD-L1. Issue 2 (7th October 2020) - Chen, Zhanfei; Chen, Yiyin; Peng, Lirong; Wang, Xiaoqian; Tang, Nanhong
Abstract : Background: 2, 5-dimethylcelecoxib (DMC) is a targeted inhibitor of microsomal prostaglandin E synthase-1 (mPGES-1), a key enzyme in the PGE2 synthesis pathway of inflammatory mediators. Previous studies have confirmed that DMC can inhibit the growth of hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC). However, it is not known whether DMC is involved in the changes of tumor immune microenvironment. Methods: In this study, we explored the effects of DMC on HBV-related HCC immune microenvironment, and deeply analyzed its unique effect and mechanism on programmed death receptor 1 (PD-1)/and its ligand 1 (PD-L1) pathway. Results: Clinical hepatoma tissues detection showed that compared with non-virus-related HCC, the level of CD8 of HBV-related HCC was significantly lower, while the levels of PD-L1 and CD163 were higher. In vivo experiments indicated that DMC could increase the level of tumor infiltrating CD8 + T cells in hepatitis B virus X (HBx) (+) hepatoma cells implanted mouse models, and inhibit the expression of PD-L1 and CD163 in tumor tissues. DMC combined with atezolizumab had more significant antitumor effect and stronger blocking effect on PD-1/PD-L1 pathway. Mechanism studies have shown that DMC can promote ubiquitin degradation of HBx-induced PD-L1 protein in HCC cells by activating adenosine 5′-monophosphate-activated protein kinase pathway. Further experiments confirmed that this process was mainly mediated by E3 ligase RBX1. Conclusions: Our results uncover a role for DMC in promoting HBV-related HCC immune microenvironment, which not only enrich the relationship between inflammatory factors (mPGES-1/PGE2 pathway) and immunosuppression (PD-L1), but also provide an important strategic reference for multitarget or combined immunotherapy of HBV-related HCC.